ANALYSIS OF PURCHASING DECISIONS FOR ADIDAS SPORTSWEAR BASED ON CELEBRITY ENDORSERS AND BRAND IMAGE - Alfifto; Siti Alhamra Salqaura; Wan Rizca Amelia; Haryaji Catur Putera Hasman (CV. Radja Publika, 2023)
The purpose of this study was to determine and analyze the influence of Celebrity Endorser and Brand Image on the Purchasing Decision Adidas Sportswear at Students of the Faculty of Economics and Business, University of Sumatera Utara and also to find out and analyze the most dominant factors affecting purchasing decision. This research was conducted at the Students of the Faculty of Economics and Business, University of Sumatera Utara. The population in this study were students of the Faculty of Economics and Business, University of Sumatera Utara. The sampling technique in this study was accidental sampling. The sample in this study is 81 students. The analytical method used is descriptive analysis method and multiple linear regression analysis method. This type of research is associative research and the data used are primary data and secondary data obtained through the study of documentation and a list of questions whose measurements use a Likert scale. Data is processed statistically using the SPSS, namely the t test model, f test and determinant coefficient (R2). The results of this study indicate that simultaneously Celebrity Endorser and Brand Image have a significant effect on Purchasing Decisions. Partially, the Celebrity Endorser and Brand Image have a positive and significant effect on Purchasing Decisions. Celebrity endorsers have the most dominant influence in influencing purchasing decisions.